2009
DOI: 10.1149/1.3089976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluorine Plasma Treatment on the Electronic Structure of Plasma-Enhanced Atomic Layer Deposition HfO[sub 2]

Abstract: We investigated the effects of fluorine treatments on the electrical properties and electronic structures of plasma-enhanced atomic layer deposition HfO 2 gate oxides, depending on the treatment process. Pre-and postoxide-deposition fluorine treatments were carried out using CF 4 plasma. Improved dielectric properties were achieved by predeposition treatment, while degradation of electrical properties was observed for postdeposition treatment. Based on the electronic structure analysis using X-ray photoemissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…3(a), which supports that fluorine incorporation in the high-k dielectric is effective only for the plasma treatment after the deposition of the high-k dielectric, basically consistent with the result in Ref. 23. The not-so clear F 1s peak of the Pre-F sample indicates less F incorporated at/near the high-k/GaAs interface and thus less passivation of dangling bonds there, leading to larger D it than that of the Post-F sample as supported by the data in Table I.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3(a), which supports that fluorine incorporation in the high-k dielectric is effective only for the plasma treatment after the deposition of the high-k dielectric, basically consistent with the result in Ref. 23. The not-so clear F 1s peak of the Pre-F sample indicates less F incorporated at/near the high-k/GaAs interface and thus less passivation of dangling bonds there, leading to larger D it than that of the Post-F sample as supported by the data in Table I.…”
Section: Resultssupporting
confidence: 90%
“…The Pre-F sample shows the largest leakage current (7.04 Â 10 À4 A/cm 2 at gate voltage of 1 V) probably because the predeposition F treatment induces radiationrelated damage to the GaAs surface and also results in excess F interstitials at the interface in the form of gap states. 17,23 In order to clarify the effects of the fluorine treatment, the chemical states in the dielectric layer and at/near the high-k/GaAs interface after the whole fabrication process are analyzed by XPS. Figure 2 shows the XPS spectrum for Ta 4f.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmas can be used for substrate pretreatment (e.g. oxidation by an O 2 plasma 69,70,119,122,130,132,149 and nitridation by NH 3 or N 2 plasmas 119,129,132 ), substrate cleaning, 98 post-deposition treatments, 141,164 and reactor wall conditioning and cleaning. 240 For example, a layer of TiN covering the walls of the reactor can be removed easily by running a F-based plasma such as one generated in NF 3 or SF 6 .…”
Section: F More Processing Versatility In Generalmentioning
confidence: 99%
“…122,130,132 The use of a CF 4 plasma for 60 s was also proven to be beneficial prior to the deposition process. 141 Maeng et al reported interface defect passivation by Si-F bonds resulting in a decrease in the flatband voltage and a lower leakage current density. The deposition of HfO 2 on a 1.0 nm thick plasma-nitrided HfO 2 or Al 2 O 3 layer was found to result in a thinner interfacial layer, a lower EOT, a lower leakage current density, and a reduced charge defect density.…”
Section: High-k Dielectric Layersmentioning
confidence: 99%
“…The extraction of capacitance equivalent thickness ͑CET͒ values and interface state density ͑D it ͒ is described in our previous reports. 12,13 Figure 1͑a͒ shows XPS spectra in Al 2p binding energy region for as-deposited and HTA ͑T a = 800°C͒ HfO 2 samples with Al 2 O 3 top layer ͑Si/ HfO 2 / Al 2 O 3 ͒. For both samples, Al 2p peak is observed clearly at 75 eV, indicating the presence of Al 2 O 3 top layer.…”
mentioning
confidence: 99%